In the shadow of the sun - O'Brien, Anne Sibley (Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Twelve-year-old Mia is on a five-day tour of North Korea with her older brother, Simon, and their father, Mark, an food aide worker, but she is scared because her father keeps sneaking off at night, and terrified that her brother's sullen, rebellious behavior (which has absolutely nothing to do with the Koreans) is going to get them in trouble--and things get much worse when she is pulled into a deadly political game that seeks to expose North Korean atrocities, and her father is arrested.